2014
DOI: 10.1080/00140139.2014.943302
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of sciatic pain and measures of internal spinal load in professional drivers

Abstract: In a prospective cohort study of professional drivers, measures of internal spinal load were better predictors of the occurrence of sciatic pain than the measures of daily vibration exposure established by the EU Directive (2002). Herniated lumbar disc, lumbar trauma and physical work load were also associated with sciatic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Excessive spinal loads have been recognized as a risk factor of back pain (Bovenzi et al, 2015;Coenen et al, 2013;Marras et al, 1995) and disc degeneration (Adams et al, 2000;Rannou et al, 2004;Stokes and Iatridis, 2004). Thus, greater BWs that yield larger (BW normalized)…”
Section: Interpretationsmentioning
confidence: 99%
“…Excessive spinal loads have been recognized as a risk factor of back pain (Bovenzi et al, 2015;Coenen et al, 2013;Marras et al, 1995) and disc degeneration (Adams et al, 2000;Rannou et al, 2004;Stokes and Iatridis, 2004). Thus, greater BWs that yield larger (BW normalized)…”
Section: Interpretationsmentioning
confidence: 99%
“…A further analysis was also carried out of the VIBRISKS data using the results from the present investigation (Bovenzi et al 2013. This provided an initial approach to epidemiological verification of the new proposals.…”
Section: Introductionmentioning
confidence: 86%
“…There was a significant trend of increasing occurrence of both 7-day and 12-month sciatic pain with the increase of S ed and R factor treated as continuous variables; such a trend was not observed for A(8) and VDV. (Bovenzi et al 2013) The results of the re-analysis showed that the measures of internal lumbar load calculated according to ISO/CD 2631-5 (S ed , R factor) were better predictors of the occurrence of sciatic pain than those of daily vibration exposure (A(8), VDV) established by the EU Directive on mechanical vibration. (Bovenzi et al 2013) However, there could be a simple alternative to R for the risk assessment of lifetime vibration exposure.…”
Section: Dynamic Forces S Ed and R -Influence Of Acceleration Postumentioning
confidence: 95%
See 2 more Smart Citations